2018
DOI: 10.1158/1078-0432.ccr-17-2754
|View full text |Cite
|
Sign up to set email alerts
|

HER3-Mediated Resistance to Hsp90 Inhibition Detected in Breast Cancer Xenografts by Affibody-Based PET Imaging

Abstract: 2 Translational RelevanceCurrently, inter-and intra-tumor heterogeneity is a clinical challenge, as histological techniques can fail to provide a representative indication of molecular variation, due to dependence on the section of tumor that is chosen for sampling. This underscores the need to introduce novel imaging biomarkers that allow the examination of the whole tumor mass and may significantly help to better understand and treat cancer. Therefore, we have developed a novel PET radiotracer that will prov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 53 publications
0
23
0
1
Order By: Relevance
“…HER3 has evolved into an important molecular target in cancer. We and others have previously investigated the potential of radiolabeled affibody molecules as HER3-targeted imaging agents for PET and SPECT [15,16,[20][21][22]27]. It has been shown that an increase in the negative charge of the radionuclide-chelator complex can improve tumor-to-liver contrast for affibody molecules [26,36].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HER3 has evolved into an important molecular target in cancer. We and others have previously investigated the potential of radiolabeled affibody molecules as HER3-targeted imaging agents for PET and SPECT [15,16,[20][21][22]27]. It has been shown that an increase in the negative charge of the radionuclide-chelator complex can improve tumor-to-liver contrast for affibody molecules [26,36].…”
Section: Discussionmentioning
confidence: 99%
“…[ 89 Zr]Zr-DFO-Z HER3:8698 3 h pi reached a tumor-to-liver ratio of 1.18 ± 0.13. However, some release of the 89 Zr label was observed in vivo, resulting in a two-fold decrease in tumor uptake after 24 and, therefore, a decrease in tumor-to-liver contrast [22]. Compared with [ 111 In]In-Z HER3 -DOTAGA [26], tumor uptake of [ 57 Co]Co-(HE) 3 -Z HER3 -DOTA was slightly lower (3.4 ± 0.5 vs. 2.4 ± 0.4% ID/g at 24 h), but tumor-to-liver contrast of [ 57 Co]Co-(HE) 3 -Z HER3 -DOTA was higher at both time points, providing another argument for using cobalt-55 as a long-lived radiolabel for PET imaging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice were administered the radioconjugate (12 µg in 100 µL of 0.9% sterile saline, 1.1-1.8 MBq/mouse) by intravenous tail vein injection and were anesthetized using an isoflurane/O 2 mixture (1.5%-2.0% v/v) approximately 5 min prior to imaging. Whole-body static PET images were acquired 1 h post-radioconjugate injection for the duration of 10 min, with a 358 to 664 keV energy window, followed by CT acquisition as previously described [26]. The image data were processed and reconstructed as previously reported [26].…”
Section: In Vivo Evaluationmentioning
confidence: 99%